The differences in career well-being among Indonesian school counselors based on educational qualifications - Muhammad Fiqri Syahril; Yusi Riksa Yustiana; Yaya Sunarya (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2023)
This study aims to describe the career well-being of school counselors in Indonesia. This study was conducted quantitatively using a quantitative descriptive analysis. The population of this study was all school counselors in Indonesia. The selection of population was made by the researchers because there is no standard Career well-being Scale in the Indonesian context. The sample consisted of 1,000 school counselors throughout Indonesia, selected using simple random sampling technique. The data was collected using the Career Well-Being Scale based on Coetzee’s theory. The study began with the development of the Career Well-Being Scale, followed by the distribution of the scale through Google Form, data collection, and data analysis. Data analysis was performed using percentage statistical formula. The results showed that the difference in career well-being of school counselors had a Sig value of 0.00. Obtaining a Sig value < 0.05 indicates that there is a significant difference in the career well-being of school counselors with four different educational qualifications. Educational qualifications influence the career well-being of Indonesian school counselors. School counselors with a master’s degree and a PPG certification have higher career well-being than school counselors with a bachelor’s degree